(untitled) (CIPEEX, 2026)
Introduction: Pain, defined as an unpleasant sensory and emotional experience, is recognized as the fifth vital sign due to its impact on individuals’ well-being and quality of life. In Brazil, pain is one of the main reasons for hospitalization, being an important cause of suffering and high costs for the healthcare system. Given this, this study aims to analyze the characterization and management of pain in order to optimize treatment and more effectively direct public health resources. Objectives: To analyze the hospitalization profile and pain management in the city of Anápolis-GO, in 2022, to understand the processes involved. Methods: A descriptive and quantitative study using secondary data from DATASUS (Health Information and Operations System) referring to Hospital Admission Authorizations (AIHs) issued in Anápolis in 2022 related to pain diagnoses. Results: There was a predominance of short-term AIHs and emergency care. Women had more short-term hospitalizations, while men had long-term hospitalizations for chronic pain. Emergency care predominated in patients aged 15 to 49 years for acute pain and over 50 years for chronic pain. Conclusions: The predominance of short-term AIHs may be a limitation of the system itself. Furthermore, the frequent use of emergency services for chronic pain points to failures in primary care. Therefore, further studies are needed, based on more complete data, to correlate procedures with pain management and evaluate the implementation of interdisciplinary programs.